Private military companies: assisting the transnational capitalist class in accumulation by dispossession - Aarseth, Tori (AUC Knowledge Fountain, 2012)
The topic of this thesis is the privatization of security and military services, and how the emergence of a private military industry should be understood. The argument I put forward has two integrated components. The first has to do with the ways in which privately provided security differs from publicly provided security, and the second with how privatization of security affects the distribution of power between social classes. I argue that privately provided security differs from publicly provided security in three main ways. First, the provision of security is depoliticized and turned into a technical issue that should be dealt with by experts only. Second, the objects to be secured are VIPs and selected areas controlled by those who have the means to pay for security, rather than national territories as a whole. Third, the implication of this shift from collective to individual security is that there will be more insecurity over all. These systematic differences in security provision mean that privatization of security is a trend which benefits the transnational capitalist class (TCC) exclusively. In order to substantiate my argument, I examine the activities of private military companies (PMCs) in Colombia and Iraq. In both countries, PMCs have been used by their national governments, foreign governments carrying out military interventions there, and transnational corporations. I found that PMCs constitute a uniquely suited tool to further capitalist interests through military means while keeping their activity and its purpose behind a veil of secrecy. They also provide a mechanism through which money can be transferred from public coffers to private hands, and through which states at the receiving end of military intervention can be made to pay for their own subjugation. PMCs should thus be understood as a tool for assisting the TCC in accumulation by dispossession abroad, rather than as a technical or cost-saving improvement as neoliberal ideology purports.